Response of sweetpotato to the combined application of organic and inorganic fertilizers in marginal upland - Ratilla, Berta C.; Bagarinao, Jay-Ar P.; Capuno, Othello B. (Annals of Tropical Research, 2018)
Marginal uplands are characterized by low soil fertility and crop productivity. To alleviate the problem, organic amendments combined with inorganic fertilizer were tested to assess their effects on the growth and yield performance of sweetpotato; determine the option treatment combination; and assess the soil physicochemical properties. A Randomized Complete Block Design (RCBD) was used with 3 replications and 7 treatments, namely: T0 = (0-0-0); T1 = 1 t ha-1 Evans + 30-30-30 kg N, P2O5, K2O ha-1; T2 = 1 t ha-1 Wellgrow + 30-30-30 kg N, P2O5, K2O ha-1; T3 = 15 t ha-1 chicken dung alone; T4 = 10 t ha-1 chicken dung + 30-30-30 kg N, P2O5, K2O ha-1; T5 = 15 t ha-1 Vermicast alone; and T6 = 10 t ha-1 Vermicast + 30-30-30 kg N, P2O5, K2O ha-1. Application of 10 t ha-1 of either chicken dung or vermicast plus 30-30-30 kg N, P2O5, K2O ha-1 in Inopacan, Leyte produced higher total root yield over the control. Root yield during the second cropping greatly increased to 16.19 t ha-1 which is almost 3 times higher than the first crop when 15 t ha-1 chicken dung alone (T3) was used. In Sta. Rita, Samar, most of the growth, yield, and yield parameters of sweetpotato were not affected by the treatments. Moreover, only a slight improvement in soil properties was noted.